PERAN DAN TANGGUNG JAWAB DEWAN PENGAWAS SYARIAH PADA LEMBAGA PERBANKAN SYARIAH DI INDONESIA - Shadriyah Shadriyah; Akmal Ihsan (Islamic Economic and Business Journal, 2022)
This article examines the roles and responsibilities of the Sharia Supervisory Board (DPS) for the practice of Islamic banking in Indonesia. This paper is considered important because seeing the current phenomenon, there are still some sharia banks that deviate from sharia principles, such as poor governance that harm customers. This study uses a normative approach with legal review, namely the laws and fatwas of the DSN-MUI. The results show that SSB acts as an agency that provides education to internal auditors to carry out internal sharia reviews related to the management of Islamic banks. In addition, SSB also functions as a mediator between Sharia Banking and the National Sharia Council in making fatwas. The responsibility of DPS is to ensure and supervise the suitability of the operational activities of a Sharia Bank according to the role of DSN-MUI and to submit all periodic monitoring reports to DSN. For the sake of perfecting the roles and responsibilities of SSB, maqashid sharia must also be considered, taking into account the aspects of religion (al- din), soul (an-nafs), minds (al-aql), property (al-mal) and descendants (an- nasl) so that the benefit is maintained and get blessings from rahamatan lil alamin.